الإدمان على المخدرات: الأسباب والعلاج: دراسة ميدانية في مدينة بغداد - رشيد، سعاد حميد (كلية العلوم الإنسانية والاجتماعية, 2021)
The phenomena od drugs addiction is considered a world very dangerous world phenomena and a real threat for the societies that effected by it for its great influence on the human, social and economic societies structures that cause the fail of individual heath, losing his mind, losing his awareness and occupation, fall of dignity, family disunited, waste of his social dignity then the drug addict becomes dependent on his family and on society instead of becoming a productive and active power to serve and advance of his society. That evoke us to make this research in aim to lean the reasons behind the addiction and methods of treatment. The most important results of this study 1- The field study explained that the age on which the subjects began to addict drugs is between (17-21) years in (42%). 2- About the feeling of the drug addict in enjoy and ecstasy, it is the first signs of desire and attraction to enter the world of addiction with the rate of (42%) for this item. 3- The subjects of sample that the friends and bad companions influence have a great role in drug addiction in (52%). 4- (85%) of the subjects stated that the society has disguised and humiliation look at them and that has bad reflection on their behavior and personalities. 5- The most important reasons that cause drug addiction are family problems as it reached (26%) followed by psychological pressures that the drug addict as a result to frustration in work o in study as it reached (22%). 6- The most important programs that help and contribute in treatment from addiction that are the most of psychological programs were it reached (26%) The most important recommendations of this study are: 1- Comprehensive enlighten for the people especially of juveniles and youths in all various audiovisual mass media and social media and space channels to evoke them to avoid this epidemic. 2- Establish rehabilitation to treat the addicts and made them avoid the adductors from dealing with drug dealers and traders for the damages on the drug addict person personality. 3- Impose strict supervision on drug smuggling and buy it in markets and watching public places cafés and city quarters in which the juveniles and young people addict the drugs. 4- Intensify sport, cultural and social activities in social and sport clubs and evoke juveniles and young people to attend them to practice activities in order to support psychological, social, religious and recreation aspects.
تعد ظاهرة تعاطي المخدرات مشكلة عالمية بالغة الخطورة وذات تهديد حقيقي للمجتمعات التي ابتليت بها وذلك لتأثيرها الكبير على نسبة المجتمعات الإنسانية والاجتماعية والاقتصادية مما يؤدي إلى هدم صحة الفرد وذهاب عقله وفقدان وعيه ووظيفته وانحطاط كرامته وتفكك أسرته وهدر كرامته الاجتماعية ومن ثم يصبح المدمن عالة على أسرته وعلى المجتمع بدلاً من أن يكون قوة منتجة وفاعلة في خدمة مجتمعه وتقدمه، هذا ما دفعنا إلى إجراء هذا البحث بهدف البحث على التعرف على أسباب الإدمان وطرق علاجه، أما أهم النتائج التي توصلت إليها الدراسة. 1- بينت دراستنا الميدانية أن العمر الذي بدأ المبحوثين بتعاطي المخدرات من (17-21) سنة وبنسبة (42%). 2- أما بخصوص الشعور المتعاطي بالمتعة والنشوة وهذا أول علامات الرغبة والجذب نحو الدخول إلى عالم الإدمان إذ بلغت النسبة (41%) لهذه الفقرة. 3- أكد المبحوثين من وحدات العينة أن تأثير الأصدقاء ورفقاء السوء كان لهم دور كبير من التعاطي المخدرات وبنسبة (52%). 4- وذكر (85%) من المبحوثين أن نظرة أفراد المجتمع نظرة احتقار واستهزاء نتيجة إدمانهم على المخدرات وما يعكسه على سلوكهم وشخصيتهم. 5- أما من أهم الأسباب التي أدت إلى التعاطي هي المشكلات الأسرية إذ بلغت النسبة (26%) وتليها الضغوط النفسية التي يتعرض لها نتيجة الإحباط في العمل أو الدراسة فقد بلغت (22%). 6- أما أهم البرامج التي ساعدت وسهمت في العلاج من الإدمان والتي لها الغالبية هي البرامج النفسية إذ بلغت النسبة (26%) أما عن أهم التوصيات التي جاءت بها الدراسة فهي: 1- التوعية الشاملة للمواطنين ولاسيما من الأحداث والشباب بجميع وسائل الإعلام ومواقع التواصل الاجتماعي المختلفة الرئيسة والمسموعة والفضائيات لحثهم على تجنب هذه الآفة. 2- إنشاء المراكز التأهيلية لعلاج المدمنين وعدم زج المتعاطين منهم مع مروجي وتجار المخدرات لما لها من أضرار على شخصية المتعاطي. 3- العمل على فرض الرقابة المشددة على تهريب المخدرات وبيعها في الأسواق ومراقبة الأماكن العامة والمقاهي والأحياء التي يتعاطى فيها الأحداث والشباب المخدرات. 4- تكثيف الأنشطة الرياضية والثقافية والاجتماعية في النوادي والأندية وتشجيع الأحداث والشباب على ارتيادها لممارسة الأنشطة لتعزيز الجانب النفسي والاجتماعي والديني والترويجي.
Keywords: المشكلات الأسرية -- ظاهرة الإدمان -- الطرق العلاجية -- الرعاية المجتمعية -- بغداد